1983
DOI: 10.1007/bf00279414
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the carrier state for an X-linked disorder, the Lesch-Nyhan syndrome, by the use of lymphocyte cloning

Abstract: Using a limiting dilution technique, we found that the frequency of thioguanine resistant (TGR) lymphocyte clones was less than 5.0 X 10(-5) in 14 normal individuals, between 9.0 X 10(-3) and 8.9 X 10(-2) in seven heterozygotes for Lesch-Nyhan syndrome, and 0.88 and 0.87 in two hemizygotes. TGR clones from heterozygotes were expanded and had the hemizygote phenotype as evidenced by low hypoxanthine incorporation and severely deficient hypoxanthine-guanine-phosphoribosyl-transferase activity. Enumeration of TGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Although several methods have been devised for the detection of the heterozy gous state for Lesch-Nyhan syndrome [1,[3][4][5], the detection of the heterozygotes of partial HGPRT deficiencies has been un successful [17]. Since even the carriers of the genes for Lesch-Nyhan syndrome con tain 5-40% HGPRT-negative peripheral T cell populations [1], heterozygotes for the non-Lesch-Nyhan HGPRT deficiencies are likely to have higher percentages of the enzyme-negative T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several methods have been devised for the detection of the heterozy gous state for Lesch-Nyhan syndrome [1,[3][4][5], the detection of the heterozygotes of partial HGPRT deficiencies has been un successful [17]. Since even the carriers of the genes for Lesch-Nyhan syndrome con tain 5-40% HGPRT-negative peripheral T cell populations [1], heterozygotes for the non-Lesch-Nyhan HGPRT deficiencies are likely to have higher percentages of the enzyme-negative T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The carrier state for abnor mal genes of Lesch-Nyhan syndrome caused by the deficiency of hypoxan thine-guanine phosphoribosyltransferase (HGPRT) [2] had been detected by the method using cultured fibroblasts or hair roots from predisposed females [3,4], However, we exploited a recently devel oped T cell culture technique using interleukin-2 for detecting the carrier state, which enabled us to make the diagnosis faster and easier [1]. Dempsey et al [5] also utilized peripheral T cells for the same purpose. A similar method detecting non functional adenine phosphoribosyltransferase in T cells has turned out to be also useful for the diagnosis of a special type of 2.8-dihydroxyadenine lithiasis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The HPRT enzyme is ubiquitous and catalyzes reactions involved with purine nucleotide salvage in mammalian cells. It also binds and ribophosphorylates many toxic purine analogs including 6-thioguanine, which allows for the in vitro selection of mutant T cells that have acquired an HPRT mutation in vivo (11)(12)(13). In addition, the HPRT gene is an excellent biomarker of effect because mutations at the HPRT locus have no direct clinical consequences and have been shown to reflect genome-wide mutational events (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Using a cloning assay similar to the one in the present work, Dempsey et al [1983] reported that 1-9% of lymphocytes in the blood of seven obligatory carriers of L-N-mutation was TG-resistant. This is a fivefold reduction from the theoretically expected level of 50% for such carriers.…”
Section: Discussionmentioning
confidence: 82%